Incarcerated Trocar Site Herniation of the Small Bowel following Laparoscopic Myomectomy - William Kondo; Monica Tessmann Zomer; Andresa Braga-Baiak; Rafael Menezes de Azevedo (Hindawi Limited, 2013)
Small bowel herniation through the fascial defect created by the entry of trocars is one of the major complications of the laparoscopic surgery. In this paper, we describe a 42-year-old woman developing an incarcerated trocar site herniation of the small bowel following laparoscopic myomectomy and treated by laparoscopic approach.